Perceptions and knowledge regarding quality and safety of plastic materials used for food packaging - Macena, Morgana (2022)
The objective of this study is to investigate the consumer perceptions about quality and safety of foods packed in plastic, as well as the impact of plastic materials on human health. To carry out the study, a questionnaire survey about the consumption habits and knowledge about plastic packaging was conducted to a sample of 487 Portuguese adult citizens. The results revealed that most respondents (81%) think about food safety and quality when purchasing foods. Additionally, it was found that the consumer’s knowledge about the toxicity of components possibly migrating from the plastic packaging to the food is still limited (only 46% of participants). However, other negative effects of plastics well known to consumers include environmental pollution and marine fauna degradation (67 and 82% of participants, respectively). Thus, it was concluded that the Portuguese population need to be further educated about the toxicity of some chemical compounds present in plastic packaging, which can be ingested by migrating to the food or which can be absorbed from the environmental microplastics resulting from incorrect disposal.